Optimization of Drinking Water Supply System Management Lanny Jaya District - Tabo, Alus (Riwayat: Educational Journal of History and Humanities, 2025)
With the increasing population in Lanny Jaya District Tiom District, the Lanny Jaya District Government through the PUPR Office has prepared a Clean waterpipeline network in the Tiom Ollo district of Giari Kali Ninu Village. However, based on performance audit data in 2023, service coverage only reached 9,989 people or 1.05% of the population. This is worrying, because Ninu spring has a discharge capacity of 114 ltr/s, which should be able to serve the entire population in Tiom District, Lanny Jaya Regency. This study will examine the potential use of Ninu Spring to overcome the problem of clean water services in Tiom District and the obstacles faced so that the coverage of clean water services is not maximized.This research is quantitative research. The research is limited to Lanny Jaya Regency and the financial feasibility study analysis is limited to the NPV (Net Present Value) and IRR (Internal Rate of Return) methods. The results showed that the NPV is positive, indicating that the value of the project investment is smaller than the amount of income from the construction of the Lanny Jaya Regency Raw Water Intake so that it can be concluded that the development is feasible. The amount of IRR value in the Raw Water Intake Development of Lanny jaya Regency was obtained at 12%. This IRR value is much greater than the interest rate set at 10%, so it is concluded that the project is feasible to build. By paying attention to the research, recommendations are obtained to carry out maintenance, optimization of piping networks and intakes that are temporarily under construction.